2020
DOI: 10.14311/ap.2020.60.0185
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characteristics, Mechanical and Wear Behaviour of Aluminium-Alloyed Ductile Irons Subjected to Two Austempering Processes

Abstract: The effect of aluminium addition and austempering processes on the microstructures, mechanical and wear properties of rotary melting furnace processed ductile irons was investigated. Ductile irons containing 1−4 wt.% Al were produced and subjected to single and two-step austempering processes. Optical microscopy was used to characterize the graphite features and estimate the volume fraction of the matrix phases present, while the x-ray diffractogram was also carried out to analyse the samples. Mechanical and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, all heattreated microstructures showed graphite nodules and carbides immersed in an ausferritic matrix of the Al-alloyed austempered ductile cast irons (AADCI) with no variations observed on their characteristics [1,6,23]. The earlier works of Adebayo et al [12,23] had reported the presence of theformation of some intermetallics compounds which showed the presence of Al-carbide phases in all the samples that contain Al as indicated in the form of intermetallic compounds of Al such as Al4SiC4,Al4C3 and MgAl2C2; in addition to Fe3C and Fe2C. This correlates and validates the carbide formation reported by Pimentel [26] on Niobium carbide and Chromium carbides (as eutectic of M3C) that were formed from the addition of Nb and Cr to cast iron.…”
Section: Microstructural and Phase Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all heattreated microstructures showed graphite nodules and carbides immersed in an ausferritic matrix of the Al-alloyed austempered ductile cast irons (AADCI) with no variations observed on their characteristics [1,6,23]. The earlier works of Adebayo et al [12,23] had reported the presence of theformation of some intermetallics compounds which showed the presence of Al-carbide phases in all the samples that contain Al as indicated in the form of intermetallic compounds of Al such as Al4SiC4,Al4C3 and MgAl2C2; in addition to Fe3C and Fe2C. This correlates and validates the carbide formation reported by Pimentel [26] on Niobium carbide and Chromium carbides (as eutectic of M3C) that were formed from the addition of Nb and Cr to cast iron.…”
Section: Microstructural and Phase Evaluationmentioning
confidence: 99%
“…Diverse works on various properties of austempered ductile cast iron (ADCI) and Aluminium-alloyed austempered ductile cast iron (AADCI) have been widely circulated. These include contact and bending fatigue behaviour; microstructure and abrasion wear behavior, wear and friction behaviors [12]. Pereira et al [13]studied the mechanical properties such as ultimate tensile strength (UTS), yield strength (YS), elongation); Brinell hardness (HB) and microstructures of austempered ductile cast iron (ADCI) alloyed with Cu-Ni-Mn-Mo in hot air austempering cycles in a two-step mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…%, and 3.74 wt. % Al [24]. Ibrahim et al [18] studied the hardness, oxidation resistance and damping capacity of Al-alloyed (up to 16 wt.…”
Section: Introductionmentioning
confidence: 99%